Atratividade da carreira docente: um estudo em uma escola da rede pública de ensino de um município da grande São Paulo - Lima, Tânia de (2010)
The central focus of this paper is the research and analysis of the interests of young people from the third year of high school, related to the choice as for whether or not opting for the teaching profession. In the same way, we intended to reflect upon the reasons that have led young people not to opt for the teaching profession and especially in the area of mathematics. The questions that guided this study were: what are the factors that determine the choice for the teaching profession by graduating students of the third year of high school, from a public school in great São Paulo? How do these students perceive the teaching profession in mathematics, and how they see it as a possibility for a future career choice? The theoretical references were based on Tenti-Fanfani and Juarez Dayrell for the understanding of the adolescent and young adult, Silvio Bock, in what refers to career choices, for the analysis, the study was based on Vygotsky, Dussel, Charlot, Candau and Roldão. The study s subjects were 122 students graduating from the third year of high school in a public school, in a city of São Paulo ABC region. The research was developed in two phases. At first instance, data collection, with the application of a questionnaire, and then, seven written records and a discussion group composed by ten students were carried out. Data revealed that these young people praise the profession, recognize it as crucial in shaping their character, but for the vast majority it does not represent a possible career choice. Such being the case, data allows us to verify that part of the non choice is associated with the romantic vision of the profession: love, talent, vocation, patience and on the other hand it has influences of social, cultural and institutional framework, implemented in the working conditions, devaluation of the profession and low income. For them, math is difficult, complicated and just for those liking it. They justified the non choice with intrinsic aspects because the discipline is boring, complicated and difficult to learn. The math teacher, according to these students, is someone who opted for this profession because he / she is a genius, loves challenges and calculations. We conclude that there is a real need to develop policies and actions to concretely promote the appreciation of the teaching profession, actions that may attract young people to this career and keep them in the profession